Study of graphene oxide-polymer nanocomposite (GPN) adsorptive membrane for lead removal from wastewater - Nik Abdul Ghani, Nik Rashidah; Jami, Mohammed Saedi; Engliman, Nurul Sakinah; Amosa, Mutiu K.; Isa, Mohamed Hasnain (School of Engineering. Taylor’s University, 2021)
The utilisation of polymeric membrane has been reported in numerous investigations on wastewater management of heavy metals. In this work, graphene oxide-polymer nanocomposite (GPN) adsorptive membranes were fabricated via non-solvent induced phase inversion (NIPS) method for lead removal. The modification of polyethersulfone (PES) membrane was conducted by incorporating graphene oxide (GO) in the matrix polymer solution. The characterisation of the GPN membranes were investigated through porosity, scanning electron microscopy (SEM) and atomic force microscopy (AFM). Optimisation of batch adsorption experiments on the GPN membrane fabricated with 0.5 wt.% of GO with the addition of 0.5 wt.% of polyvinylpyrrolidone (PVP) exhibited the highest lead removal that is about 97.81% under 60 minutes exposure and acidic condition (pH 5). Langmuir isotherm model was found to be the best-fitting for the lead adsorption process. The findings indicated that the monolayer adsorption mechanism occurred on the surface of the GPN membrane.